The Role of Nursing Staff in the Care of Pediatric Patients in the Postoperative Period (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Nursing care of patients in the postoperative period is a prerequisite for quality recovery of a person who has undergone surgical intervention. At this time, the patient is in an incapacitated state, unable to care for himself. His body is weakened, and he himself needs professional care and rehabilitation. In addition, the risk of postoperative complications is high.